Using Scaffolding to Support Students’ English Speaking: What Does The Teacher Think? - Ade Tika; Utami Dewi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to explore the scaffolding instruction used in developing students’ speaking and describe the teacher's perspective after using scaffolding to support and help students develop their English speaking skills. A qualitative descriptive research method was used in this study that aims to describe the situation observed in the field more precisely, transparently, and in-depth. The focus of this study was one English teacher in a primary school. In collecting the data, the researcher conducted semi-structured interviews and observations to obtain the teacher’s perception and the instructional scaffolding used in teaching speaking. Then in analyzing data, the researcher adopts Miles and Huberman's (1994) method consisting of data reduction, data display, and conclusion or drawing. The results showed that the types of scaffolding used by the researcher in teaching English were two types: modelling and bridge, and then the positive and negative effects were provided. Significantly, this study can be used as a reference in supporting students to develop their speaking skills through instructional scaffolding.